Answer:
C. -18
Explanation:
The value of the expression is found by substituting the given value for the variable and following the Order of Operations to evaluate it.
__
![(2(4(6-t)^2+t-3(t+5)))/(3)\qquad\text{given}\\\\=(2(4(6-6)^2+6-3(6+5)))/(3)=(2(4(0^2)+6-3(11)))/(3)=(2(6-33))/(3)\\\\=(2(-27))/(3)=(-54)/(3)=\boxed{-18}](https://img.qammunity.org/2023/formulas/mathematics/high-school/n7y02wroxuz2blvcirzf24bkp2k6ajpcpg.png)
_____
Additional comment
In this instance, the Order of Operations can be shortcut a bit by factoring 3 from the numerator and denominator early in the evaluation.
= 2(2 -11) = 2(-9) = -18